2019
DOI: 10.3390/ijms20030743
|View full text |Cite
|
Sign up to set email alerts
|

Design of Novel Oligomeric Mixed Ligand Complexes: Preparation, Biological Applications and the First Example of Their Nanosized Scale

Abstract: A successful oligomerization of ternary metal complexes, cobalt (II), nickel (II), copper (II), zinc (II), chromium (III) and ferric sulfate (III) with nitrilotriacetic acid (NTA) as a primary ligand and glutamic acid as a secondary ligand, has been demonstrated. The formation of oligomers arose from the presence of the sulfate moiety, which operates as a bridged bidentate ligand that coordinates with other metal moieties. The novel oligomers exhibited octahedral structures, which bonded together through the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…In a similar pattern, Pip, a nitrogen-based ligand, shows coordination to the metal ions through the amine N and the Cl as evidenced by the disappearance of the band 3286 cm -1 attributable to the amine N with Δ value of 147 cm -1 , and also the hypsochromic shift of C-Cl band at 650 cm -1 in the ligand to 662 cm -1 in the metal complexes, indicating the possibility of coordination through the Cl group. These rationally suggest the ligand to act as a bidentate ligand (16) The electronic spectra, magnetic moment, and elemental analysis results of the synthesized metal complexes are reported in Table 3 (17,30,31). The presence of the ligands in the complexes as proposed (Schemes 1 & 2) was supported with good consistency between the CHNS elemental analysis results (Supplementary file) and the suggested molecular formulas.…”
Section: Research Articlesupporting
confidence: 52%
See 2 more Smart Citations
“…In a similar pattern, Pip, a nitrogen-based ligand, shows coordination to the metal ions through the amine N and the Cl as evidenced by the disappearance of the band 3286 cm -1 attributable to the amine N with Δ value of 147 cm -1 , and also the hypsochromic shift of C-Cl band at 650 cm -1 in the ligand to 662 cm -1 in the metal complexes, indicating the possibility of coordination through the Cl group. These rationally suggest the ligand to act as a bidentate ligand (16) The electronic spectra, magnetic moment, and elemental analysis results of the synthesized metal complexes are reported in Table 3 (17,30,31). The presence of the ligands in the complexes as proposed (Schemes 1 & 2) was supported with good consistency between the CHNS elemental analysis results (Supplementary file) and the suggested molecular formulas.…”
Section: Research Articlesupporting
confidence: 52%
“…Therefore, this study aims at the preparation of coordination compounds consisting of Co(II) and Cu(II) ions in complex with sodium NaD and Pip as mixed ligands using solvent-based inorganic synthetic approach, characterization and evaluation of antioxidant and antibacterial activity in vitro as well as some in silico biological studies, while adopting some reported protocols (10,(14)(15)(16)(17)(18) with modifications.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…in the greatest amount, their content was 1.56 μg/mg (1.29% from total content amino acids), 1.16 μg/mg (0.96%) and 0.92 μg/mg (0.76%), respectively. L-glutamic acid participates in many metabolic reactions, is a source of glucose, and holds its level in the blood (Okasha et al 2019). Also, this acid is used as a conjugate because its effectiveness of anticancer medicine is better and reductions of its toxicity in attitude to normal cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the improved biological properties of chelates over their precursor ligands, chelation also leads to formation of a more stable metal-organic framework. The choice of the metal connectors and the bridging ligands permits the utilization of these materials in areas, such as ion exchange, adsorption and separation processes; heterogeneous and biomimetic catalysis; sensor technologies; luminescence; drug delivery; and proton conductivity (Okasha et al, 2019). The metal-organic coordination macromolecules exhibit remarkable stability in comparison to their discrete complexes due to their macrocycle or chelate effect.…”
Section: Introductionmentioning
confidence: 99%